1998
DOI: 10.1083/jcb.141.2.539
|View full text |Cite
|
Sign up to set email alerts
|

Rho-mediated Contractility Exposes a Cryptic Site in Fibronectin and Induces Fibronectin Matrix Assembly

Abstract: Many factors influence the assembly of fibronectin into an insoluble fibrillar extracellular matrix. Previous work demonstrated that one component in serum that promotes the assembly of fibronectin is lysophosphatidic acid (Zhang, Q., W.J. Checovich, D.M. Peters, R.M. Albrecht, and D.F. Mosher. 1994. J. Cell Biol. 127:1447–1459). Here we show that C3 transferase, an inhibitor of the low molecular weight GTP-binding protein Rho, blocks the binding of fibronectin and the 70-kD NH2-terminal fibronectin fragment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
567
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(598 citation statements)
references
References 71 publications
(144 reference statements)
20
567
0
Order By: Relevance
“…Our results suggest that integrins may (1) mediate cell adhesion in such a way as to control display of FN assembly sites, (2) interact with conformationally changed FN to enable fibril progression and (3) transduce force to the elongated and assembled FN to stretch the molecules and open individual type III modules, thus allowing FN-FN interactions that result in the SDS-non-dissociable complexes (Baneyx et al, 2002;Ohashi et al, 2002;Zhong et al, 1998). In agreement with these ideas, a FN construct lacking the RGD sequence was found to bind in "short stitches" on FN−/− cells cultured on collagen in 72-h assays (Sottile et al, 2000), indicating that binding to integrins via the RGD region is not essential for binding of full length FN to cell surfaces but is important for fibril progression.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our results suggest that integrins may (1) mediate cell adhesion in such a way as to control display of FN assembly sites, (2) interact with conformationally changed FN to enable fibril progression and (3) transduce force to the elongated and assembled FN to stretch the molecules and open individual type III modules, thus allowing FN-FN interactions that result in the SDS-non-dissociable complexes (Baneyx et al, 2002;Ohashi et al, 2002;Zhong et al, 1998). In agreement with these ideas, a FN construct lacking the RGD sequence was found to bind in "short stitches" on FN−/− cells cultured on collagen in 72-h assays (Sottile et al, 2000), indicating that binding to integrins via the RGD region is not essential for binding of full length FN to cell surfaces but is important for fibril progression.…”
Section: Discussionmentioning
confidence: 80%
“…Bound 70K co-localizes with preexisting FN fibrils (Chernousov et al, 1985), albeit incompletely (Zhang et al, 1994). 70K also binds to FN that is adsorbed to surfaces and subjected to tension (Zhong et al, 1998). Thus, the N-terminal region of FN has been proposed to mediate binding to stretched or otherwise conformationally altered FN molecules (Hocking et al, 1994(Hocking et al, , 1996WierzbickaPatynowski and Schwarzbauer, 2003;Zhong et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type I collagen assembles passively into matrix by self-polymerization (32), although certain proteins, including other collagen types, fibromodulin, lumican, decorin, and tenascin, can modify this process (33)(34)(35). In contrast, fibronectin matrix assembly is an active process and requires several conditions: an intact intracellular cytoskeleton, an activated fibronectin-binding integrin receptor, and tension across the developing fibrillar structure (36,37). Investigators in our group showed previously that TGF␤ and PDGF stimulate fibronectin matrix assembly, possibly through changes in integrin receptor activity (29).…”
Section: Discussionmentioning
confidence: 99%
“…The conformations Fn assumes on synthetic surfaces, however, are rather distinct from those of native Fn in soluble and fibrillar forms (reviewed in Antia et al, 2006;Baugh and Vogel, 2004;Halter et al, 2005). Fn polymerization into fibers is thought to proceed as cryptic self-assembly sites are exposed by cell contractility (Baneyx and Vogel, 1999;Mao and Schwarzbauer, 2005;Ohashi et al, 1999;Zhong et al, 1998).…”
Section: Introductionmentioning
confidence: 99%